Lagenorhynchus cruciger - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lagenorhynchus cruciger (Quoy and Gaimard 1824) [Delphinus] cruciger Quoy and Gaimard 1824, Voy. autour du Monde. l'Uranie et la Physicienne, Zool.: 87. Type Locality: Pacific Ocean, "entre la Nouvelle-Hollande et le cap Horn [= between Australia and Cape Horn].par 49 [S] de latitude". Vernacular Names: Hourglass Dolphin. Synonyms: Lagenorhynchus albigena (Quoy and Gaimard 1824); Lagenorhynchus bivitattus (Lesson and Garnot 1826); Lagenorhynchus clanculus Gray 1846; Lagenorhynchus wilsoni Lillie 1915. Distribution: Southern hemisphere: antarctic and cold-temperate waters. Conservation: CITES – Appendix II; IUCN – Lower Risk (lc). Discussion: Formerly included australis and obscurus , see Hershkovitz (1966 a ) and comments under australis and obscurus . Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 730, DOI: 10.5281/zenodo.7316519